Cytomegalovirus Viral Load Kinetics in Patients with HIV/AIDS Admitted to a Medical Intensive Care Unit: A Case for Pre-Emptive Therapy - Mayaphi, Simnikiwe H. (Public Library of Science, 2014)
BACKGROUND: Cytomegalovirus (CMV) infection is associated with severe diseases in immunosuppressed patients; however, there is a lack of data for pre-emptive therapy in patients with HIV/AIDS. METHOD: This was a retrospective study, which enrolled patients diagnosed with HIV/AIDS (CD4<200 cells/μl), who had detectable CMV viral load (VL) during their stay in an adult medical intensive care unit between 2009–2012. RESULTS: After screening 82 patients’ records, 41 patients met the enrolment criteria. Their median age was 37 (interquartile range [IQR]: 31–46), and median CD4 count was 29 cells/μl (IQR: 5–55). Sixteen patients (39%) had serial measurements of CMV VL before treatment with ganciclovir. Patients whose baseline CMV VL values were between 1,000–3,000 copies/ml had significantly higher values (median of 14,650 copies/ml) on follow-up testing done 4–12 days later. Those with undetectable VLs at baseline testing had detectable VLs (median of 1,590 copies/ml) mostly within 20 days of follow-up testing. Patients who had VLs >1,000 copies/ml at baseline testing had significantly higher mortality compared to those who had <1,000 copies/ml {hazard ratio of 3.46, p = 0.003 [95% confidence interval (CI): 1.55–7.71]}. Analysis of the highest CMV VL per patient showed that patients who had VLs of >5,100 copies/ml and did not receive ganciclovir had 100% mortality compared to 58% mortality in those who received ganciclovir at VLs of >5,100 copies/ml, 50% mortality in those who were not treated and had low VLs of <5,100 copies/ml, and 44% mortality in those who had ganciclovir treatment at VLs of <5,100 copies/ml (p = 0.084, 0.046, 0.037, respectively). CONCLUSION: This study showed a significantly increased mortality in patients with HIV/AIDS who had high CMV VLs, and suggests that a threshold value of 1,000 copies/ml may be appropriate for pre-emptive treatment in this group.